Evaluation of Factors of Competitiveness of Light Industries in Regions (European Journal of Economics, Finance and Business Development, 2024)
In this article, in order to evaluate the factors of competitiveness of light industries, a questionnaire was conducted among the enterprises that are members of the "Uztoqimachiliksanoat" association and the "Uzbekcharmpoyabzali" association of textile, sewing-knitting and leather industry enterprises of Uzbekistan operating in the Zarafshan region. The questionnaire consisted of 37 questions representing factors grouped into 5 groups and 3 free questions.